Application of Moringa oleifera seeds and Musa cavendish as coagulants for lead, nickel and cadmium removal from drinking water - Ab Aziz, Nur Adila; Jayasuriya, Niranjali; Fan, Linhua (IOP Publishing, 2015)
Contamination of drinking water sources by heavy metals in many South Asian countries has become a major public health concern. As conventional chemical treatment of the contaminated water may not be feasible for many remote communities in the region due to technical and financial constraints, some low-cost, native and abundantly available natural materials have emerged as a potential alternative to the expensive water treatment chemicals. Plant-based materials 'Moringa oleifera' (MO) and 'Musa cavendish' (MC) were investigated in this study as the coagulants for removing lead (Pb), nickel (Ni) and cadmium (Cd) from groundwater containing metal ions at their typical concentrations found in selected South Asian countries. Coagulation tests were conducted with the individual coagulants and their combinations on synthetic and real groundwater samples. The best removal efficiencies for Ni (77%) and Cd (67%) were achieved by the combined coagulants dosed in a mixing manner at the optimum coagulant dosages of 200+200 mg/L from the initial concentration of 31 mug/L and 5 mug/L, respectively. This was attributed to the presence of additional binding sites with different active functional groups, leading to higher removal efficiency compared to the individual coagulant. However, MO alone showed the best removal for Pb (87%) at the coagulant dose of 300 mg/L from the initial concentration of 19 mg/L; suggesting that MO had a good affinity towards Pb. The study demonstrated that MO and MC have the potential to remove Pb, Ni and Cd from drinking water to meet the World Health Organisation (WHO) drinking water standards.